A novel remaining useful life prediction method based on multi-support vector regression fusion and adaptive weight updating. (December 2022) - Li, Yuxiong; Huang, Xianzhen; Zhao, Chengying; Ding, Pengfei
Abstract: Remaining useful life prediction is of huge significance in preventing equipment malfunctions and reducing maintenance costs. Currently, machine learning algorithms have become hotspots in remaining useful life prediction due to their high flexibility and convenience. However, machine learnings require large amounts of data, and their prediction performance depends heavily on the selection of hyper-parameters. To overcome these shortcomings, a novel remaining useful life prediction method for small sample cases is proposed based on multi-support vector regression fusion. In the offline training phase, the fusion model is established, consisting of multiple support vector regression sub-models To obtain the optimal sub-model parameters, the Bayesian optimization algorithm is applied and an improved optimization target is formulated with various metrics describing regression and prediction performance. In the online prediction phase, an adaptive weight updating algorithm based on dynamic time warping is developed to measure the fitness of each sub-model and determine the corresponding weight value. The C-MAPSS engine dataset is used to test the performance of the proposed method, along with some existing machine learning methods as comparison. The proposed method only requires 30% of the training data sample to achieve high accuracy, with a root mean square error of 14.98, which is superior to other state-of-the-art methods. The results demonstrate the superiority of the proposed method. Highlights: A multi-support vector regression fusion model is proposed for remaining useful life prediction. The Bayesian optimization algorithm with improved optimization target is applied for parameter selection. An adaptive weight updated algorithm is proposed to measure model fitness. The proposed method can achieve high accuracy with fewer data sample. The effectiveness is validated by aero-engine dataset.